Examining the effect of agency cost on capital structure-financial performance nexus: empirical evidence for emerging market - Shirwan Rafiq Sdiq; Hariem A. Abdullah (Cogent Economics & Finance)
Despite the long history of testing agency theory, it is yet standing undefeated. This study examines the relationship between capital structure and firm performance in an emerging economy, Iraq. Moreover, it seeks to find an answer for the question “does agency cost moderates the relationship between capital structure and financial performance?” in the case of a developing industrial sector. Data was collected from published financial statements from the Iraqi Stock Exchange. The study sample consists of several companies from industrial sector listed on ISX over the period 2004–2020. Firm performance is measured using both accounting data and market indicator. Agency cost is measured through operating expense ratio and asset utilization ratio. Testing for short-term and long-term parameters between groups, pooled mean group estimation method is used for data analysis. The results manifest evidence to support agency theory in explaining the relationship between capital structure and financial performance. Moreover, strong interactions are found indicating that agency cost has a considerable impact on the capital structure and firm performance association, that is, agency cost moderates the relationship between capital structure and firm performance. These results are robust checking various methods and diagnostics checks. These results are key evidence from an emerging country, Iraq to support the agency theory arguments. The results provide significant insights for managers of the sector particularly for the current rapid development in the sector.